Interaction and meaning making in teacher literature circles / Angeline Ranjethamoney a/p Vijayarajoo - Vijayarajoo, Angeline Ranjethamoney (2015)
This study investigates interactions among three in-service teachers, in a teacher literature circle [TLC], as they tried to make sense of a new literature text, which they had to teach to their students. The new text was introduced by the Ministry of Education in Malaysia in 2011 and the teachers needed to make sense of it first. It is within this context that the researcher studied the ways in which teachers made meaning of the new text through their interactions in the teacher literature circles. This study addresses the following questions: How do teacher interact ion a TLC during discussions of a new literature text and how do teachers make meaning of the new text? The participants comprised three experienced teachers, who had taught the English language syllabus since the introduction of the literature component. The study addresses the interaction between the three in-service teachers as they discussed the new literature text in teacher literature circles. The teachers discussed the new literature text, “Catch Us If You Can” by Catherine Macphail. Data collection comprised transcripts of teacher literature circle discussions, group and individual interviews, written participant reflection forms and researcher field notes. The data were analyzed, described and interpreted, to show the processes and complexities involved in trying to make sense of the new literature text through the interactions of the teacher during the TLC. Findings showed that in-service teachers in TLCs played multiple roles – that of facilitator, leader, active listener etc. The review of literature shows that these roles were also played out by the teachers in classroom with their students. Apart from these roles, the talk was exploratory in nature where the teachers supported one another in their collaborative efforts to understand the new text. During the teacher interactions, various themes arose helped the teachers to negotiate meanings of the text. This make sense of the text. The research offers insights into the complexities of teacher interactions and the multi-tiered nature of the meaning making processes of teachers as they make sense of a new literature text in a teacher literature circles.